1969
DOI: 10.1063/1.1671028
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 2.8-eV Tritium Atoms with Methane

Abstract: Tritium atoms with 2.8-eV kinetic energy have been formed by 1849-Å photolysis of TBr, and have been reacted with CH4 in the presence of Br2. In addition to HT from the abstraction reaction known in thermal systems, the direct substitution of T for H to form CH3T has been observed. The ratio of HT/CH3T is 3.6 to 4.0 in low Br2 mole fraction. In Br2 mole fractions exceeding 0.5, this ratio is reduced to 3.0, and the absolute yields of both HT and CH3T are greatly reduced. The formation of HT and CH3T from hot r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

1971
1971
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 60 publications
2
11
0
1
Order By: Relevance
“…1͒. ͑This isomerization or exchange process was also deduced from much earlier ''hot atom'' experiments by Rowland et al͒ 2 From the branching ratio between normal and exchanged products, Lovejoy and Moore used a simple kinetic model to extract separately the unimolecular rate constants for direct dissociation ͑i.e., H 2 CϭCЈϭO→H 2 CϩCЈϭO without isomerization͒ and for isomerization, k d (E) and k iso (E), respectively. In a series of articles, 3 Moore et al have reported on many other interesting aspects of ketene photodissociation that are not the subject of the present article.…”
Section: Introductionmentioning
confidence: 99%
“…1͒. ͑This isomerization or exchange process was also deduced from much earlier ''hot atom'' experiments by Rowland et al͒ 2 From the branching ratio between normal and exchanged products, Lovejoy and Moore used a simple kinetic model to extract separately the unimolecular rate constants for direct dissociation ͑i.e., H 2 CϭCЈϭO→H 2 CϩCЈϭO without isomerization͒ and for isomerization, k d (E) and k iso (E), respectively. In a series of articles, 3 Moore et al have reported on many other interesting aspects of ketene photodissociation that are not the subject of the present article.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the qualitative effect of this collisional dissociation on the HT yield in gas phase recoil tritium moderation studies, the HT produced in the computer simulated reaction, (1), was allowed to collide with rare gas atom until either it had dissociated or its total energy 1.0 Ρ 0.6 ' HT 0.2 8 16 32 eV 64 Translational energy Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…and K. it can be seen that this implied that HT was formed, in the main, at lower average energies than RT [1, 2], This was not an unexpected finding since Η-abstraction was known to have a lower threshold than H-substitution [8], and indeed was the only process observed at thermal energies.…”
Section: Ht 'Rtmentioning
confidence: 98%
See 2 more Smart Citations